Characterization of nanoscale rockmechanical properties and microstructures of a Chinese sub-bituminous coal - Zhang, Y.; Lebedev, Maxim; Al-Yaseri, A.; Yu, H.; Xu, X.; Iglauer, Stefan (Elsevier Inc., 2018)
© 2018 Elsevier B.V. Microstructures and geomechanical properties are of key importance in coal mining, coal bed methane production and CO 2 storage in deep coal seams. Full characterization of the microstructures needs multiscale methods and accurate mechanical data to avoid geohazards (e.g. coal seam layer collapse, fault reactivation or methane leakage). However, standard methods (i.e. acoustic, seismic or USC tests) measure only cm-km bulk properties, while it is clear that the nano-micrometre scale coal heterogeneity plays a vital role. Thus, we used the SEM, microCT, and NMR to characterized the microstructure of a Chinese sub-bituminous coal, and measured nanoscale geomechanical properties via nanoindentation tests and compared the results with the traditional acoustic method. We found that such coal had few cleats, while nanopores constituted the main pores. Furthermore, clear heterogeneity in geo-mechanical properties was observed and mapped, which was not reflected in the bulk acoustic measurements (which provide only averaged data). Such small scale heterogeneity, however, clearly highly correlated with the morphology of the sample, where the mineral phase in the coal had higher indentation moduli (up to 60 GPa for well consolidated), while the coal matrix had lower indentation moduli (lower than 6 GPa). We conclude that such nanoscale rockmechanical property was highly correlated with the morphology of the microstructure; and importantly, it is necessary to measure geomechanical coal properties at small scale to appreciate their large variation and highly heterogeneous character, and to reliably assess and eventually reduce the risk of geohazards.